2018
DOI: 10.1002/chem.201803080
|View full text |Cite
|
Sign up to set email alerts
|

The Dual‐State Luminescent Mechanism of 2,3,4,5‐Tetraphenyl‐1H‐pyrrole

Abstract: 2,3,4,5-Tetraphenyl-1H-pyrrole (TePP) was synthesized by a simple one-step reaction. The compound showed a balanced emission in both the solution and solid state with the absolute quantum yield of Φ =65.6 % and Φ =74.3 %, respectively. Temperature and viscosity variation measurements demonstrated that the phenyl group at the 1-position (N-position) of the pyrrole core can act as a rotor in pyrrole-based molecules, which can consume the excited energy and reduce the molecular emission in solution. TePP without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…To overcome this issue, in 2001, Ta ng and co-workersp roposed an ew concept of "aggregation-induced emission" (AIE), [26] in which AIE luminogens (AIEgens) usually exhibit no or poorly emissivec haracteristics in dilute solution, but emit intensely in the aggregated state. [27][28][29][30][31] By using these highly emissive AIEgens, dual-state emission can be easily achieved and they have potential real-world applications, [32][33][34] such as in PA detection and LFP visualization. Recently,f lexible alkyl chains were introduced into conventionalf luorescent molecules to prevent close packing of their core structures as well as strong p-p intermolecular stacking interactions, [35][36][37] thereby openingr adiative channels to afford highlye missive features in aggregates.T herefore, based on these considera-tions, to achieve ah ighly efficient dual-state emission platform for PA detection and LFP visualization,i nt his work, flexible alkyl chains were facilelya ttached to the commercial organic dye 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA)t o afford the tetraalkyl 3,4,9,10-perylenetetracarboxylate target compounds PTCA-C4, PTCA-C6, and PTCA-C12 (fort he structures, see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, in 2001, Ta ng and co-workersp roposed an ew concept of "aggregation-induced emission" (AIE), [26] in which AIE luminogens (AIEgens) usually exhibit no or poorly emissivec haracteristics in dilute solution, but emit intensely in the aggregated state. [27][28][29][30][31] By using these highly emissive AIEgens, dual-state emission can be easily achieved and they have potential real-world applications, [32][33][34] such as in PA detection and LFP visualization. Recently,f lexible alkyl chains were introduced into conventionalf luorescent molecules to prevent close packing of their core structures as well as strong p-p intermolecular stacking interactions, [35][36][37] thereby openingr adiative channels to afford highlye missive features in aggregates.T herefore, based on these considera-tions, to achieve ah ighly efficient dual-state emission platform for PA detection and LFP visualization,i nt his work, flexible alkyl chains were facilelya ttached to the commercial organic dye 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA)t o afford the tetraalkyl 3,4,9,10-perylenetetracarboxylate target compounds PTCA-C4, PTCA-C6, and PTCA-C12 (fort he structures, see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results demonstrated that the phenyl group at the 1-position of the pyrrole ring acts as a rotor, consumes the excited state energy and lowers the emission in solution. 27 Therefore, the increase in the rotational barrier at the 1-position will effectively restrict the intramolecular motion allowing the materials to have bright fluorescence in solution (Scheme 1). This strategy can change the TPP-based molecules with both AIE and ACQ properties to molecules with DSE properties by simply extending the conjugation length at the 1-position of the pyrrole molecule.…”
Section: Dse Properties Of Tpp-based Compoundsmentioning
confidence: 99%
“…Recently, our group developed a series of polyarylpyrroles such as triphenylpyrrole isomers (TPP-1,2,4, TPP-1,2,5 and TPP-1,3,4), tetraphenylpyrrole (TePP) and pentaphenylpyrrol (PPP) (Scheme 1). [25][26][27] Their AIE and ACQ as well as DSE properties were determined by the position of the corresponding phenyl substitution. 27 A phenyl group attached to the 1-position of the pyrrole ring can act as a rotor that consumes the energy of the excited state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations